Application of In-situ Thermal Regeneration Technology in Southern Ring Section of Guangzhou Ring Expressway. (June 2020) - Peng, Chenchu; Yang, Fang; Feng, Liu
Abstract: Based on the South Ring Section of Guangzhou Circum-City Expressway, the characteristics of in-situ thermal regeneration and pavement regeneration technology are analyzed. The pavement performance of the mixture is evaluated by means of immersion residual stability, rutting and freeze-thaw splitting test. The application effect of in-situ thermal regeneration pavement is evaluated by means of seepage test and structural depth test. The results show that the water stability and high temperature stability of recycled asphalt mixture after adding recycling agent are in line with the specifications; the segregation of recycled pavement is large, the seepage is serious, and the seepage and structural depth of overlay recycled pavement meet the requirements; this paper summarizes the application experience and problems in the application process, and provides a reference for similar projects. Basis and improvement direction.